PENGEMBANGAN DESA WISATA BERBASIS PARTISIPASI MASYARAKAT LOKAL DI DESA WANASARI - ARIE FITRIANTI; AHMAD YUNANI (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The aims research are (1) to know rele and sinergity managerial local community on tourism village know rele and sinergity managerial local community on tourism village in Wanasari village (2) to know obstacles or problems of community on development tourism village in Wanasari village.This research do in Wanasari village, Sungai Loban district, Tanah Bumbu regency. Tehnical collection data uses depth interview and observational direct. Technical analysis data use descriptive qualitative with triangulation analysis. The result research show role of community Wanasari village in planning development of tourism village are very greatly which like the community help to help clean culture tourism center and developing community like art or dance then community too donation their money or some of plants or vas to tourism village, then role of government and private sector has significant effect because local government given funds to build infrastructure to tourism village and private sector investment to supporting economic activity village.Keyword: Tourism, Tourism Village, Local Community, Community Based Tourism